2007
DOI: 10.1128/aem.00897-07
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Characterization of theListeria monocytogenesCold Regulon in Log- and Stationary-Phase Cells

Abstract: Whole-genome microarray experiments were performed to define the Listeria monocytogenes cold growth regulon and to identify genes differentially expressed during growth at 4 and 37°C. Microarray analysis using a stringent cutoff (adjusted P < 0.001; >2.0-fold change) revealed 105 and 170 genes that showed higher transcript levels in logarithmic-and stationary-phase cells, respectively, at 4°C than in cells grown at 37°C. A total of 74 and 102 genes showed lower transcript levels in logarithmic-and stationary-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 104 publications
12
120
2
1
Order By: Relevance
“…In agreement with previous reports (Chan et al, 2007;Liu et al, 2002), cold stress dependent lmo0501 mRNA induction could also be detected in the present study. In addition an lmo0501 transcriptional induction was detected in response to lactic acid and NaCl osmotic stresses.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with previous reports (Chan et al, 2007;Liu et al, 2002), cold stress dependent lmo0501 mRNA induction could also be detected in the present study. In addition an lmo0501 transcriptional induction was detected in response to lactic acid and NaCl osmotic stresses.…”
Section: Discussionsupporting
confidence: 94%
“…One of the putative cold adaptation genes identified in this bacterium is the lmo0501 locus of L. monocytogenes EGDe, which codes for the putative transcription activator protein Lmo0501. An increase in lmo0501 mRNA is observed in transcriptomes of cold acclimated L. monocytogenes cells (Chan et al, 2007;Liu et al, 2002). The aim of the present study was to examine lmo0501 gene functional contributions in adaptation of L. monocytogenes cells to cold, NaCl salt and organic acid stress associated with preserved food.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among these are compatible solute transporters encoded by the opu and gbu operons; oligopeptide permease encoded by oppA; ferritin (Fri); and phosphohydrolase, encoded by pgpH and involved in ppGpp turnover (7,9,20,23,28,41,42,45,46). L. monocytogenes harbors 4 putative DExD-box RNA helicases, and in a previous study, the genes encoding three RNA helicases (lmo0866, lmo1450, and lmo1722) were found to be induced at low temperatures (11). A transposon insertion in a region directly upstream of a putative RNA helicase gene (homologous to lmo1722) in L. monocytogenes strain F2365 induced a cold-sensitive growth phenotype and reduced swarming motility on soft agar plates (4).…”
mentioning
confidence: 89%
“…Likewise, L. monocytogenes strains that harbor a transposon insertion in pghH, encoding a putative metal-dependent phosphohydrolase (118), are cold sensitive and contain increased levels of ppGpp. Furthermore, at 4°C, stationary-phase L. monocytogenes cells contain lower levels of relA transcript than do their log-phase counterparts rather than the higher levels usually associated with stress tolerance (42). Therefore, L. monocytogenes may decrease its ppGpp pool to adapt to the cold temperatures encountered in refrigerated food products.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%